2015
DOI: 10.1021/acs.iecr.5b02365
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Pyrolysis Process for Producing High Quality Bio-oils

Abstract: A newly developed two-step pyrolysis process for the fractionation of lignocellulosic biomass components into sugar-rich and lignin-derived rich bio-oils by using pinewood as the feedstock has been studied. In the first step, biomass is pyrolyzed between 300°C and 350 o C decomposing cellulose and hemicellulose fibers to produce bio-oil having significantly higher selectivities towards sugars and lower selectivities towards low molecular weight oxygenated compounds, such as organic acids, aldehydes, and ketone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…Levoglucosany ield can be altereda nd secondary reactions suppressed significantly by optimizing the following experimental variables:s ample size, carrier/sweep gas rate, heating rate, and biomass moisture content. [16,17,[60][61][62][63][64][65] It was demonstrated that H-ZSM-5, with aS i/Al ratio of roughly3 0, gives the best selectivity to aromaticsc omparedt oa morphous silica-aluminas, other zeolites,a nd other supported metal or metal oxide catalysts. Thus, slow heating rates maximize the amount of useable levoglucosan.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Levoglucosany ield can be altereda nd secondary reactions suppressed significantly by optimizing the following experimental variables:s ample size, carrier/sweep gas rate, heating rate, and biomass moisture content. [16,17,[60][61][62][63][64][65] It was demonstrated that H-ZSM-5, with aS i/Al ratio of roughly3 0, gives the best selectivity to aromaticsc omparedt oa morphous silica-aluminas, other zeolites,a nd other supported metal or metal oxide catalysts. Thus, slow heating rates maximize the amount of useable levoglucosan.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
“…Selectivity to aromatic products or value-added chemicals was determined to be af unction of catalyst/biomass weightr atio, heating rate, pore size, reactorc onfiguration, and reactiontemperature. [16,17,[60][61][62][63][64][65] It was demonstrated that H-ZSM-5, with aS i/Al ratio of roughly3 0, gives the best selectivity to aromaticsc omparedt oa morphous silica-aluminas, other zeolites,a nd other supported metal or metal oxide catalysts. [60,63,[66][67][68][69][70][71] However, physical mixtures of Siral 5, an amorphous silica-alumina, and H-ZSM-5 was shown to have as ynergistic effect on the yield of aromaticsr elative to either catalystalone.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
“…Zinc chloride (ZnCl2) is one of the promising catalysts to produce furfural (FF) [19]. Zinc chloride is known to affect the fast pyrolysis reaction of biomass [19], but the exact effect on fast pyrolysis of pinewood is not well known [20,21]. Qiang Lu and Zhi Wang published an article on zinc chloride impregnated corncobs and its effect on the product yield distribution from the pyrolysis.…”
Section: Zinc Chloride (Zncl2) For Catalytic Pyrolysismentioning
confidence: 99%
“…Proximate analysis was done using the same procedure as described in prior research studies [61][62][63][64][65]. Ultimate analysis was obtained using the Parikh, J. et al correlation [66], along with HHV [67].…”
Section: Characterization Of Biomass Samplesmentioning
confidence: 99%